The Division Of Gono-Gini's Property from The Credit Agreement with The Deed Under The Hand Between The Husband and Wife and The Outstanding Creditor Is Associated with The Banking Law and The Notary Office Law - Fathalya Laksana; Fransiscus Xaverius Arsin (LEGAL BRIEF, 2022)
The Banking Law does not explain the regulation regarding the form of credit agreement in the banking world, it must be made in the form of an underhand agreement or must use an authentic deed made before a notary. Meanwhile, the Notary Position Act only regulates private agreements and the authority of a notary in making authentic deeds, but does not specifically regulate credit agreements made in the form of notarial or private deeds. The purpose of this study is to analyze how the validity of private credit agreements is seen from the Banking Act and UUJN as well as arrangements for the distribution of gono-gini assets for couples who have divorced from the results of private credit agreements between husband and wife and creditors who have not been paid off. To answer the main problems in this study, the author uses a juridical - normative research method and is sourced from secondary data, with an emphasis on the use of library materials as a source of research. Based on the results of the author's research, the credit agreement under the hand can be said to be valid if the credit agreement is recognized by the customer. Because the legal force of an underhand credit agreement depends on the recognition of the parties, the party whose name and signature are included in the underhand deed. In addition, the distribution of gono-gini assets must be based on the principle of justice, which is to be divided equally between both parties.